KEGIATAN PENYULUHAN KESEHATAN GIGI DAN MULUT SERTA GERAKAN SIKAT GIGI YANG BAIK DAN BENAR PADA ANAK TAMAN KANAK-KANAK DOA BANGSA - Annisa, Aulia; Firdaus , Muhammad; Fariuzi; Dara Dwi Oktaviyanti; Anisya Fitri; Melfi Amanda; Salwa Innasya Sugesty (Awal Bros Journal of Community Development, 2024)
Oral health is an important aspect in maintaining quality of life, especially from an early age. Good and proper dental care habits play a major role in preventing various oral health problems. Preschool children still do not understand the importance of maintaining oral hygiene, teeth and mouth must be kept clean because germs can enter the oral cavity. Disorders that often occur in the teeth and mouth are damage to the hard tissue of the teeth which is often called dental caries. Oral health promotion is a process of providing information that arises on the basis of oral health needs that aim to produce good oral health and improve the standard of living. In oral health promotion, individuals gain experience or information through various oral health promotion media. Counseling is primarily aimed at groups vulnerable to oral health disorders, namely kindergarten children. Oral health counseling activities and proper toothbrushing movements for kindergarten children aim to increase awareness and knowledge from an early age about the importance of good oral care. This counseling was carried out at Doa Bangsa Kindergarten with a fun and easy-to-understand approach for children, using visual media such as pictures, videos, and educational games. In addition, children are taught the correct toothbrushing technique through live demonstrations by health worker students, accompanied by explanations about the benefits of maintaining dental hygiene for overall health. Dental and oral health education for children is very important because at that age their teeth grow.